The Effect of Antitrust Investigations on Discretionary Accruals: A Refined Test of the Political-Cost Hypothesis - Cahan, Steven F. (The Accounting Review, 1992)
[The antitrust laws of the United States prohibit monopolies or attempts to create a monopoly in any unregulated line of business. In the past, the two agencies that enforce these laws, the Department of Justice and the Federal Trade Commission, have relied on accounting profits in prosecuting such antitrust violations. The agencies argued that high accounting rates of return were "excessive" and indicative of monopolistic power on the part of the firm. Thus, to reduce the possibility of an unfavorable ruling and the costs associated with it, managers in firms investigated for monopoly-related violations would have incentive to use accounting procedures (e.g., accounting methods, accruals) that produce abnormally low levels of income. Because the incentive to reduce income will increase as the threat of an unfavorable ruling becomes more imminent, it is expected that managers will take additional steps to lower income while being actively investigated, compared with periods of non-investigation. The differences in political costs caused by the antitrust investigation are used to provide a refined test of the political-cost hypothesis. In particular, the study examines, on a longitudinal basis, whether managers respond to these investigations by adjusting their discretionary accruals. The discretionary accruals for 48 firms that were investigated for monopoly-related violations were estimated over a 15-year period by using the residuals of a fixed effects covariance model that regressed total accruals on the change in sales, the fixed asset balance, and dummy variables representing each firm and year. The specific hypothesis tested is whether the estimated discretionary accruals over the period of investigation (typically more than one year) were lower, or more income-reducing, than those in other years. The hypothesis was tested by using a nested design with a dummy variable, coded 1 for the years of investigation, included in the accrual model. This variable was significant and negatively signed, which indicates that discretionary accruals were lower while the firm was being investigated, as expected. The discretionary accruals for a control group of firms that were not investigated were also estimated, and these were found to remain the same during the periods of investigation and non-investigation for the matched sample firms. The results from these tests support the political-cost hypothesis and are consistent with the view that managers adjust earnings in response to monopoly-related antitrust investigations.]